Worldwide Wound Healing - Innovation in Natural and Conventional Methods 2016
DOI: 10.5772/64913
|View full text |Cite
|
Sign up to set email alerts
|

Aspects Related to Venous Ulcer Healing and its Influence on Quality of Life

Abstract: Nowadays, the varicose ulcers (VUs) are one of the most worrying leg ulcers and are an important global health problem, with high costs related to the treatment and its complications. Moreover, the quality of life (QOL) of the patient could be affected by pain, sleep disorders, functional impairment, depression, and isolation. The VU patient care is complex, and it is necessary to know the aspects that contribute to the healing process for developing effective strategies. The members of the multidisciplinary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A high percentage of our patients (86%) had pain, the symptom that occurred most often in studies on VLUs. 9-11,21-26 The relationship between pain intensity and poorer quality of life has been confirmed in various studies. 9-11,21,24-26 In these studies, patients stated that pain continuously reminded them of the wound’s presence and occasionally made them feel a loss of control over the wound.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A high percentage of our patients (86%) had pain, the symptom that occurred most often in studies on VLUs. 9-11,21-26 The relationship between pain intensity and poorer quality of life has been confirmed in various studies. 9-11,21,24-26 In these studies, patients stated that pain continuously reminded them of the wound’s presence and occasionally made them feel a loss of control over the wound.…”
Section: Discussionmentioning
confidence: 89%
“…Guarnera et al reported a poorer quality of life, measured with the Short Form 12 scale, in women with VLUs, 18 and Torres found significant differences between age and VLUs. 22…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that, because blood has such a low resistivity (1.6 Ωm -1 ), current is likely to be concentrated wherever it flows: if there is a lot of blood near the surface of the skin, current flow will concentrate near the surface, otherwise it will penetrate deeper [98]. This means that the effect of applying electrostimulation could vary depending on the blood flow to a wound, often an issue in cases of vascular ulceration [2], as well as with the ambient temperature, as blood flow is concentrated near the skin when body is trying to cool itself down [99].…”
Section: B Electrode Layoutmentioning
confidence: 99%
“…All types of wounds can become chronic, but they are most prevalent as a result of pressure or vascular ulcers. These are breaks in the skin which occur because of a lack of blood flow to the underlying tissue, caused by prolonged pressure or by other problems with the circulatory system, often associated with diabetes [1], [2].…”
Section: Introductionmentioning
confidence: 99%